10 - The 1913 Cut-off Date for Restitution of Dispossessed Land in South Africa: A Critical Appraisal - Yanou, Mike Akomaye (Africa Development, 2006)
Land is a vital resource whose ownership and control has been the most contentious issue in South Africa since the arrival of the white settler in the country. The early history of the country can, with some justification, be summed up as a gigantic struggle for land between the indigenous peoples and white settlers. The struggle for access to land remains a perennial problem in this country. This paper investigates the land restitution regime set up following the introduction of post-apartheid democratic constitutions of 1994 and 1996. It argues that the constitutional limitation on land restitution only to land dispossessed on or after the 19 June 1913 tilted the balance in the struggle over land between South Africans of African descent and those of European extraction, in the latter’s favour. This defeats the indigenous South Africans’ expectation that the ANC government will be committed to a new land policy that makes the unencumbered restoration of dispossessed land a human right.